Organoleptic and Quality Characteristics of Malagousia Variety, Grapes Fermented with Selected Indigenous Yeast Strains - Karampatea, A.; Vrhovšek, Ur.; Tsakiris, A.; Dimopoulou, M.; Kourkoutas, Y.; Skavdis, G. (South African Journal of Enology and Viticulture, 2022)
Commercial Malagousia varietal wines, which are produced in almost all Greek viticultural zones, represent a relatively important part of Greek wine activity. This study presents the results of a profile compilation of volatile aroma compounds of Malagousia musts fermented under identical conditions with selected yeast strains. In total, 62 volatile aroma compounds were identified and separated into their chemical classes (aldehydes, higher alcohols, volatile phenols, terpenes, C13-norisoprenoids, lactones, esters, fatty acids, sulphur compounds, other compounds, and other alcohols). Alcohols and higher alcohols, such as cis-hexen- 1-ol and geraniol, terpenes like linalool, esters such as ethyl isovalerate, ketones such us betadamascenone, beta-ionone and zingerone, and fatty acids such as geranic acid and phenylacetaldehyde, were found in all the samples. Among them, linalool and phenylacetaldehyde had the strongest effect on the volatile compound profile of Malagousia wines. The same wine samples were subjected to sensorial analysis by a trained panel of 10 wine tasters, and a statistical analysis of both analyses presents similarities between the two analysis approaches. It is hoped that the results will contribute to a better understanding of the quality potential of the Malagousia variety so as to evaluate possible differences on the basis of the detected aroma concentrations.